Adolescent with highly active multiple sclerosis - Huamaní, Charles (2019)
Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS) that can occur in many different ways and progresses generating disability. Less than 5% of cases are pediatric, and even less frequent are the cases of MS in aggressive or highly-active forms. We present the case of a 13-yearold boy who in six months had three attacks, each time more aggressive, with a severe disease burden evidenced by MRI and a rapid progression of his disability. We discuss the diagnostic approach of the MS in the pediatric age, its form of presentation and the evaluation of highly active MS forms.